Multi-stimuli-responsive supramolecular gel constructed by pillar[5]arene-based pseudorotaxanes for efficient detection and separation of multi-analytes in aqueous solution. Issue 42 (19th October 2018) - Zhang, You-Ming; Li, Yong-Fu; Fang, Hu; He, Jun-Xia; Yong, Bi-Rong; Yao, Hong; Wei, Tai-Bao; Lin, Qi
Abstract : A novel pseudorotaxanes-type crosslinker of a supramolecular polymer network (WP5-PN ) was constructed based on water-soluble pillar[5]arene (WP5 ) and naphthalene dimethylamine derivative (PN ) via host-guest interactions. Abstract : Here, a novel pseudorotaxanes-type crosslinker of a supramolecular polymer network (WP5-PN ) has been constructed from a host water-soluble pillar[5]arene (WP5 ) and a guest naphthalene dimethylamine derivative (PN ) via a stepwise process involving multiple non-covalent interactions. The obtained supramolecular polymers were able to transform into a supramolecular polymer gel (WP5-PN-G ) and show AIE properties in DMSO–H2 O binary solution. Interestingly, due to the dynamic and reversible nature of non-covalent interactions, the resultant supramolecular polymer gels exhibited external stimuli-responsiveness to different parameters, such as temperature, acid–base, competitive guest and mechanical stress. Moreover, WP5-PN-G showed fluorescent response for Fe 3+ and Cu 2+, while its xerogel showed excellent recyclable separation properties for these metal ions with adsorption rates up to 98.07% and 95.38%, respectively. Moreover, by rational introduction of these metal ions into theWP5-PN-G, corresponding metal ion coordinated metallogels, such asWP5-PN-FeG andWP5-PN-CuG were obtained. These metallogels could selectively and sensitively sense F − and CN −, respectively. The detection limits of these metallogels for F − and CN − were about 1 × 10 −8 M. TheWP5-PN-G has potential applications in multi-analytes detection and separation as well as fluorescent display materials.